ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), BIAYA OPERASTONAL PENDAPATAN OPERASTONAL (BOPO), NON PERFORMING LOAN (NPL), LOAN TO DEPOSIT RATIO (LDR) TERHADAP PROFITABILITAS BANK PEMBANGUNAN DAERAH - , Taufik Harwinanda Adiwena ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is performed in order to test the influence of the variable, Capital Adequacy Ratio (CAR), Biaya Operasi terhadap Pendapatan Operasi(BOPO), Non Performing Loan (NPL) ,and Loan to Deposit Ratio (LDR) toward Return on Asset (ROA). Methodology reseach as the sample was accuired 25banking company over period 2010-2011. Data analysis with multilinear regression of ordinary least square and hypotheses test used t-statistic dan F-statistic at level of significance 5%, a classic assumption examination which consist of data normality test, multicolinierity test, heteroskedasticity test and autocorrelation test is also being done to test the hypotheses. During research period show' as variable and data research was normal distributed. Based on multicolinierity test, heteroskedasticity test and autocorrelation test classic assumption deviation has not founded, tihis indicate that the available data has fulfill the condition to use multi linear regression model. Result obtained from regression with the level significansi 5% indicating that value R-Square equal to 0,487 meaning that 48,7% change of ROA influenced by CAR, BOPO, NPL, And LDR, and the rest 27,8%. Conclusion obtained by that change of CAR, BOPO and change of LDR have the influence to ROA.